Peran Mediasi Kemampuan Penyelesaian Proyek dalam Peningkatan Hasil Belajar Analisis Data - Rahmawati, Desi; Hudallah, Noor; Supraptono, Eko; Sunarko, Budi (SAP (Susunan Artikel Pendidikan), 2024)
This study aims to determine the effect of student understanding and student activity on learning outcomes in informatics subjects through the mediator of project completion ability. The study used a quantitative approach with the Structural Equation Modelling analysis method with 168 students as respondents. The data collection instrument was a questionnaire containing positive and negative statements covering indicators including, understanding (translation, interpretation, extrapolation), activity (participation, gathering information, discussion, assessing self-ability), learning outcomes (cognitive, affective, psychomotor improvements), project completion skills (problem solving, critical thinking, project management). The results showed that student understanding had a significant effect on learning outcomes (percentage 25.2%, p-value 0.001), and project completion skills (percentage 32.7%, p-value 0.000). Student activity does not affect learning outcomes (percentage of 2%, p-value 0.802), but affects the skills to complete projects (percentage 50.5%, p-value 0.000). The skills to complete projects have a significant effect on learning outcomes (percentage 57.7%, p-value 0.000). In addition, student understanding and student activity have a significant indirect effect on learning outcomes through the mediator of project completion skills with each percentage (18.9%, p-value 0.000 and 29.2%, p-value 0.000). Thus, student understanding and project completion skills have a direct effect on student learning outcomes, while student activity only has an indirect effect through project completion skills.